Efficacy and safety of valsartan compared to enalapril in hypertensive children: a 12-week, randomized, double-blind, parallel-group study - Schaefer, Franz; Litwin, Mieczyslaw; Zachwieja, Jacek; Zurowska, Aleksandra; Turi, Sandor; Grosso, Amie; Pezous, Nicole; Kadwa, Mahomed (Journal of hypertension, 2011)
Objective - This study compares efficacy and safety of valsartan with enalapril in hypertensive children aged 6-17 years. - Method - This was a 12-week, randomized, double-blind, parallel-group, active-controlled study. After a single-blind placebo run-in period (4-28 days), patients with mean sitting systolic blood pressure (BP) (MSSBP) at least 95th percentile for age, gender, and height were randomized to receive half the assigned dose for first week, and force-titrated to full dose for 11 weeks (≥18 to <35 kg - valsartan: 80 mg, enalapril: 10 mg; ≥35 to <80 kg - valsartan: 160 mg, enalapril: 20 mg; ≥80 to ≤160 kg - valsartan: 320 mg, enalapril: 40 mg). The primary efficacy variable was changed from baseline in MSSBP to show noninferiority of valsartan to enalapril. Other efficacy variables were changed from baseline in MSDBP, SBP control rate, and 24-h ambulatory BP parameters. - Results - Of 300 randomized patients, 281 (94%) completed the study. At week 12, MSSBP reductions were similar for valsartan and enalapril (primary endpoint of noninferiority, P < 0.0001). Least square mean BP reductions from baseline of −15.4/−9.4 mmHg were observed for valsartan compared with −14.1/−8.5 mmHg for enalapril. A similar proportion of patients achieved SBP control (valsartan: 67%; enalapril: 70%). In the subset of patients who underwent ambulatory BP assessments, valsartan provided greater reductions than enalapril in mean 24-h SBP (valsartan: −9.8 mmHg, enalapril: −7.2 mmHg: P - = 0.03). The overall incidence of AEs was similar (valsartan 60%, enalapril 58%) with headache, cough, and nasopharyngitis reported most frequently. - Conclusions - Valsartan and enalapril provided comparable BP reductions and effective BP control and were well tolerated in hypertensive children aged 6-17 years.